Westkunst; Zeitgenössische Kunst seit 1939. - Glozer, L. (Köln : DuMont Buchverlag, 1981)
Acconci, Vito ; Agam, Yaacov ; Albers, Josef ; Andre, Carl ; Anselmo, Giovanni ; Appel, Karel ; Arman ; Arp, Hans (Jean) ; Artaud, Antonin ; Auerbach, Frank ; Bacon, Francis ; Baldessari, John ; Balthus ; Barry, Robert ; Baselitz, Georg ; Baumeister, Willi ; Bazaine, Jean ; Beckmann, Max ; Bell, Larry ; Bellmer, Hans ; Berman, Eugene ; Beuys, Joseph ; Bill, Max ; Bissier, Julius ; Boltanski, Christian ; Brancusi, Constantin ; Braque, Georges ; Brecht, George ; Broodthaers, Marcel ; Brouwn, Stanley ; Brus, Günter ; Buren, Daniel ; Burri, Alberto ; Bury, Pol ; Butler, Reg ; Byars, James Lee ; Cage, John ; Calder, Alexander ; Calzolari, Pierpaolo ; Capogrossi, Giuseppe ; César ; Chadwick, Lynn ; Chagall, Marc ; Chamberlain, John ; Chillida, Eduardo ; De Chirico, Giorgio ; Christo ; Consagra, Pietro ; Constant ; Cornell, Joseph ; Dali, Salvador ; Darboven, Hanne ; Davis, Stuart ; Delvaux, Paul ; Dibbets, Jan ; Dine, Jim ; Domela, César ; Dubuffet, Jean ; Duchamp, Marcel ; Dufrêne, François ; Ernst, Max ; Fabro, Luciano ; Fahlström, Öyvind ; Fautrier, Jean ; Ferber, Herbert ; Filliou, Robert ; Riverhead (New York) ; Fontana, Lucio ; Francis, Sam ; Freundlich, Otto ; Gac, Jean Le ; Giacometti, Alberto ; Gilbert & George ; Glarner, Fritz ; González, Julio ; Gorky, Arshile ; Götz, K.O. (Karl Otto) ; Graeser, Camille ; Graham, Dan ; Graubner, Gotthard ; Hains, Raymond ; Hamilton, Richard ; Hartung, Hans ; Heerup, Henry ; Heiliger, Bernhard ; Heizer, Michael ; Heldt, Werner ; Hélion, Jean ; Hepworth, Barbara ; Hesse, Eva ; Hockney, David ; Hofmann, Hans ; Hopper, Edward ; Huebler, Douglas ; Immendorff, Jörg ; Johns, Jasper ; Jorn, Asger ; Judd, Donald ; Kandinsky, Wassily ; Kaprow, Allan ; Kawara, On ; Kelly, Ellsworth ; Kienholz, Edward ; Klee, Paul ; etc.
boek